The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/09537104.2015.1131255
|View full text |Cite
|
Sign up to set email alerts
|

Platelet concentrates for revitalization of immature necrotic teeth: a systematic review of the clinical studies

Abstract: This systematic review aimed at determining the effectiveness of autologous platelet concentrate (APC) in the treatment of immature necrotic teeth. An electronic search was performed on MEDLINE, Embase, Scopus, SciELO, Lilacs, CENTRAL. Comparative clinical studies were included, in which APC was tested for pulp regeneration and radicular development. Selected articles underwent risk-of-bias assessment. Clinical and radiographic outcomes were considered. Three randomized parallel studies and one split-mouth cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 52 publications
0
36
0
3
Order By: Relevance
“…However, a systematic review of clinical studies of platelet concentrations in revitalization of immature necrotic teeth demonstrated that PRP or PRF was not significantly superior to a blood clot in promoting thickening of the canal walls/continued root development in RET (Lolato et al . ). Even a combination of platelet‐rich fibrin and blood clot compared to blood clot alone did not improve outcomes of RET (Zhou et al .…”
Section: Blood Clotmentioning
confidence: 97%
“…However, a systematic review of clinical studies of platelet concentrations in revitalization of immature necrotic teeth demonstrated that PRP or PRF was not significantly superior to a blood clot in promoting thickening of the canal walls/continued root development in RET (Lolato et al . ). Even a combination of platelet‐rich fibrin and blood clot compared to blood clot alone did not improve outcomes of RET (Zhou et al .…”
Section: Blood Clotmentioning
confidence: 97%
“…Over the last decade, research has increasingly focused on the development of biology-based alternative treatment concepts such as revitalization, which aims for the regeneration of the pulp-dentine complex (Murray et al 2007) and the promotion of lengthening and thickening of dentine walls (Lolato et al 2016). The clinical outcomes of revitalization procedures have been reported to be successful (Nagy et al 2014, Lin et al 2017 with root maturation by dentine wall thickening and lengthening or apical closure (Shah et al 2008, Lolato et al 2016, Nazzal et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, research has increasingly focused on the development of biology-based alternative treatment concepts such as revitalization, which aims for the regeneration of the pulp-dentine complex (Murray et al 2007) and the promotion of lengthening and thickening of dentine walls (Lolato et al 2016). The clinical outcomes of revitalization procedures have been reported to be successful (Nagy et al 2014, Lin et al 2017 with root maturation by dentine wall thickening and lengthening or apical closure (Shah et al 2008, Lolato et al 2016, Nazzal et al 2018. However, due to the presence of ectopic tissue such as cementum and the lack of cells with a distinct odontoblast phenotype in vivo (Shimizu et al 2012, Becerra et al 2014, Lei et al 2015, the generated tissue has consequently been described as reparative tissue and not as regenerated pulp tissue (Gomes-Filho et al 2013, del Fabbro et al 2015, Saoud et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence on the benefits of the use of platelet concentrates in these pathologies exists but is still scarce. A recent systematic review concluded that periapical healing and apical closure were improved in those immature necrotic teeth treated with PRP compared with the control group without PRP, even though not statistically significant, and a significant better thickening of dentinal walls and root lengthening were also reported [35]. However, from the histological point of view, it seems that a true regeneration of necrotic pulp tissue of either mature or immature teeth was not achieved after using platelet concentrates.…”
Section: Endodontics and Endodontic Surgerymentioning
confidence: 99%